Energy matching analysis for net-zero energy buildings. (2nd October 2016) - Mohamed, Ayman; Hasan, Ala
Abstract : A net zero energy building is a grid connected building that exports as much energy as it imports over a predefined period of time based on a certain balance metric. Energy matching defines how much the building load covered with its own generation, as well as the interplay with the surrounding grids. This study aims to investigate the energy matching of a building and its effect on categorizing its net zero energy building balance options. Three common net zero energy building balance metrics are considered: site-energy, primary energy, and CO2-eq emission based on Finnish reference data. A single family house located in Helsinki, Finland served by four conventional heating systems and seven biomass-based co-generation heat and power technologies are simulated using a simulation-based model software. A photovoltaic (PV) system is a supplementary system that can bring the building to a balanced status, when needed. Energy matching is analyzed under the consideration that the building is connected with the bi-direction electrical grid. The results show that the lowest imported weighted energy does not necessarily represent the best net zero energy building case. The energy matching analysis could become another criterion for the best net zero energy building case selection. The co-generation heat and power technologies show a better energy matching situation than the conventional heating systems fulfilling all of the net zero energy building balances investigated.